Основные направления улучшения использования сырья в кондитерской промышленности - Белова, Татьяна Геннадьевна (My University, 1991)
Обоснованы основные направления улучшения использования сырьевых ресурсов в кондитерской промышленности. Дается характеристика таких направлений, как внедрение нетрадиционных видов сырья, увеличение производства нових ассортиментных групп, повышение уровня механизации и автоматизации производственных процессов. Уделяется внимание сокращению потерь сырья при транспортировке. The main directions of improving the use of raw materials in the confectionery industry are substantiated. Characteristics of such areas as the introduction of non-traditional types of raw materials, increasing the production of new product groups, increasing the level of mechanization and automation of production processes are given. Attention is paid to reducing the losses of raw materials during transportation.
Keywords: бестарная перевозка; механизация и автоматизация; рациональное использование сырья; нетрадиционные виды сырья; новые виды продукции; bulk transportation; mechanization and automation; rational use of raw materials; non-traditional types of raw materials; new products; кафедра маркетингу